Five Stages of Grief in the Song Burn from Hamilton’s Musical: A Psycholinguistics Approach - Novia, Jessica; Widianingtyas, Nugraheni (Universitas Bunda Mulia, 2023)
The concept of five stages of grief has long been acknowledged as a base to understand the emotional experience of loss. The song from Hamilton's musical,